THE DETAILS HE REMEMBERS: THE READING SPAN OF AN 8-YEAR-OLD DYSLEXIC CHILD - Kirana, Angkita Wasito (International Journal of Psychosocial Rehabilitation, 2020)
The main goal of reading is to comprehend the text by understanding all of the details stated in the text. Unfortunately, due to their lacking ability in processing the details, dyslexic readers tend to fail in recalling some of the sentence details. Thus, this research aimed to point out the reading span of a dyslexic child as well as the tendency of his answers when being asked about the sentence details. A battery of 51 sentences that consisted of evenly distributed information details such as Noun (as the Subject and Object of the sentence), Verb (as the predicate), Adjective, and Adverbs was constructed. It was accompanied by 219 comprehension questions related to each detail presented in the battery. In obtaining the data, the Participant was asked to read sentences and answers the comprehensive questions that follow each sentence. Results showed that the participant tends to make more incorrect answers as the number of details within a sentence increased. In addition, Participant tends to be able to correctly recall details that were placed in latter parts of the sentence. Also, the Participant of this study tends to fail in recalling the modifiers. Implications were discussed. The results of this research is expected to help parents and children to provide better education quality and facilities for dyslexic children as part of the inclusive education programs.